Advanced Skeletal Muscle Mass Reduction (Sarcopenia) Secondary to Neuromuscular Disease - G. R. Pesola; V. Terla; M. Pradhan (Case Reports in Critical Care)
We describe a young male patient chronically on a ventilator secondary to decreased mobility from amyotrophic lateral sclerosis (ALS). He had both a tracheostomy for breathing and percutaneous endoscopic gastrostomy (PEG) for feeding. Using 24-hour urinary creatinine excretion data, we calculated an estimate of skeletal muscle (SM) mass. SM mass was indexed to height and weight to obtain the SM index. The SM index is used as a determinant to define sarcopenia. From the data, we found that this patient had the smallest SM index ever recorded at 2.2 kg/m2, consistent with extremely advanced sarcopenia. As a comparison, “severe” sarcopenia in a male is defined as a SM index≤8.5 kg/m2. This method can be used in ICU patients to evaluate for sarcopenia which is a predictive marker for mortality.